(untitled) (Research in Agriculture Livestock and Fisheries, 2022)
The consumption of fish is accepted by all ages and social groups. Moreover, fish is rich in both micro, and macro-nutrients and minerals which are suitable for human development. The objectives of the study was to profile the socio-economic characteristics of households in Mopani District Municipality, to describe rural households’ consumption pattern of inland fisheries and, to analyse the factors that influence the consumption of inland fisheries by rural households in the study area. A total of 134 households were interviewed using structured questionnaire. Descriptive statistics, Household Dietary Diversity Score and Binary Logistic model were adopted to achieve these objectives. The results showed that Bass, Tilapia, Catfish and Carp are the most preferred inland fish species by rural households in the study area. However, Tilapia is the dominating fish species preferred by households for weekly consumption purposes. The regression results revealed that age and the gender of the household positively influence the consumption of inland fisheries while, access to inland fisheries’ market has a negative relationship with consumption. To this end, the study concludes that the inclusion of inland fisheries as food by rural households and the availability of markets are necessary for the improvement of a healthy life. Vol. 9, No. 2, August 2022: 239-246